Studi Fenomenologi Pengalaman Perubahan Citra Tubuh pada Klien Kelemahan Pasca Sroke di RSUP Dr M Djamil Padang - Novi Herawati (NERS Jurnal Keperawatan, 2014)
Stroke is a clinical syndrome of neurological deficits, which can cause death and weakness. This weakness will impact on the client's body image changes after stroke. The research purpose is to explore client experiences pasca stroke weakness at changes in body image. Descriptive phenomenological qualitative research design with in-depth interviews to 7 pasca stroke with weakness clients undergoing outpatient neurology polyclinic of Dr. M. Djamil Padang City Hospital. Data were gathered in interview recording and field note form, then transcribed and analyzed by Colaizzi’s techniques. This study identified eight themes included the decrease in function and changes in the body's ability, emotional conflict to changes in the body, changes in social activities, increased ability at changes in body image, external support at changes in body image, coping strategies used for changes in body image, family support for healing and expectations for recovery of the body. Results showed weakness affects the physical, psychological and social that potential to cause psychosocial problems. Coping strategies that used, still might have a risk of maladaptive behavior. It can be a condition of the psychosocial needs nursing care and therapy psychiatric nursing can be given proper. It is expected nurse as nursing care providers can improve the role and function as counselors and nursing care providers with caring.